2008
DOI: 10.1002/pssr.200802146
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of GaN(0001)‐2 × 2 thin films grown by PAMBE

Abstract: Gallium nitride thin films were grown on silicon carbide (0001) by plasma‐assisted molecular beam epitaxy (PAMBE). The samples were cooled down in nitrogen plasma and characterized in situ by reflection high energy electron diffraction (RHEED), photoelectron spectroscopy (XPS/UPS), and atomic force microscopy (AFM) revealing stoichiometric and smooth GaN films virtually free of contaminations. We present valence band data obtained by UPS with strong emission from surface states inside the fundamental band gap.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
29
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 14 publications
5
29
0
Order By: Relevance
“…For the 3 nm cap sample we obtain Φ B =249 meV, while Φ B =171 meV and Φ B =585 meV are found for the other two samples with 1 nm and without cap, respectively. These results emphasize the findings presented in [9][10][11] and can be interpreted by a surface Fermi-level pinning close to the conduction band edge caused by a surface donor with high density of states. We observe a significant impact of the GaN cap layer thickness on the Schottky gate behaviour in forward and reverse directions, namely the ideality factor as well as the gate and drain leakage currents.…”
Section: Impact Of Gan Cap Thicknesssupporting
confidence: 82%
“…For the 3 nm cap sample we obtain Φ B =249 meV, while Φ B =171 meV and Φ B =585 meV are found for the other two samples with 1 nm and without cap, respectively. These results emphasize the findings presented in [9][10][11] and can be interpreted by a surface Fermi-level pinning close to the conduction band edge caused by a surface donor with high density of states. We observe a significant impact of the GaN cap layer thickness on the Schottky gate behaviour in forward and reverse directions, namely the ideality factor as well as the gate and drain leakage currents.…”
Section: Impact Of Gan Cap Thicknesssupporting
confidence: 82%
“…For experimental investigations, contamination-free surfaces close to the ideal structures used in calculations are an essential requirement. In a previous work, we demonstrated the growth and the in-situ photoemission characterization of GaN(0001) surfaces showing no indications of surface contaminations [4]. These surfaces exhibit a 2×2 reconstruction which is calculated to be the most stable reconstruction except for very Ga-rich conditions [5].…”
mentioning
confidence: 94%
“…Our measurements showed that a reconstructioninduced surface state of the as-grown surface completely vanishes within 2 hours under our UHV conditions [4]. Therefore, the experimental procedure had to be adapted appropriately.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to remove excess Ga, the grown samples were held in nitrogen plasma at growth temperature for a short time after growth, thus removing the Ga adlayer. More details concerning the technical details of the used MBE system and typical growth parameters can be found elsewhere [11]. The quality of the produced samples was controlled through reflection of high-energy electron diffraction (RHEED) during the growth and after the following cooling down procedure.…”
Section: Methodsmentioning
confidence: 99%